2017
DOI: 10.1111/1751-7915.12713
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional response ofEscherichia colito ammonia and glucose fluctuations

Abstract: SummaryIn large‐scale production processes, metabolic control is typically achieved by limited supply of essential nutrients such as glucose or ammonia. With increasing bioreactor dimensions, microbial producers such as Escherichia coli are exposed to changing substrate availabilities due to limited mixing. In turn, cells sense and respond to these dynamic conditions leading to frequent activation of their regulatory programmes. Previously, we characterized short‐ and long‐term strategies of cells to adapt to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 62 publications
5
67
0
Order By: Relevance
“…The duration, frequency and magnitude of concentration gradients in an actual large‐scale bioreactor are all dynamic parameters . In effect, the exposure time in the scale‐down bioreactor should be a flexible parameter that can be changed easily, to suit a specific large‐scale bioreactor . In the current contribution, this flexibility of scale‐down design is offered by the modelling framework of the pulse‐based system.…”
Section: Discussionmentioning
confidence: 99%
“…The duration, frequency and magnitude of concentration gradients in an actual large‐scale bioreactor are all dynamic parameters . In effect, the exposure time in the scale‐down bioreactor should be a flexible parameter that can be changed easily, to suit a specific large‐scale bioreactor . In the current contribution, this flexibility of scale‐down design is offered by the modelling framework of the pulse‐based system.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic flux analysis, using a previously established stoichiometric model for growth and penicillin production in P. chrysogenum (van Gulik et al, 2000), shows that there is a 34% and 16% larger ATP gap in the IFRs of 6 min and 3 min, respectively, but in 30 s IFR, the ATP gap is nearly the same as in the chemostat cultures. Similarly, in E. coli, it has been found that the cellular energy demands for coping with fluctuating carbon or nitrogen source supply become higher under simulated large-scale conditions, due to continuous on-off switching of related genes and the increased cellular ATP costs of transcription and translation (Loffler et al, 2016Simen et al, 2017).…”
Section: Stoichiometrymentioning
confidence: 99%
“…Among them, the frequent activation of the tryptophan operon could be observed (Simen et al, 2017). The mathematical model comprising the (Equations 2–16) was used to describe not only short- and long-term transcriptional dynamics but also to estimate the impact on protein formation by linking the transcription with the translation machinery.…”
Section: Resultsmentioning
confidence: 99%
“…Transcript measurements are published in Simen et al (2017) and are available under GEO Accession GSE90743.…”
Section: Methodsmentioning
confidence: 99%